Pola Konsumsi Beras Petani Desa Rowotengah Kecamatan Sumberbaru Kabupaten Jember - Nimatul Masruroh (An-Nisa’ Journal of Gender Studies, 2016)
Nowadays the farmers in Indonesia alienates from the profession sociologically and anthropologically. It is proved that they do not want to pass their profession to their grandchildren; moreover, the farmers are not proud of their own product. They consume rice on the market (import) without considering quality and health impact as the innate of the product. They do not concern about synthetic rice in the market. The farmers in the Rowotengah village Sumberbaru district, Jember is one of the case that we met. They always sell the rice to the buyer without harvesting first. The process of harvest is done by the buyers itself. While for their daily need, they have to buy by retail in the shops. The pattern of the rice consumption which is contra-productive from the profession itself.